Akad Sistem Penggadaian Dalam Perspektif Ekonomi Syariah - Al Maghfuri, Rahmah Salsabila (Jaanur Elbarik Indonesia, 2025)
This study aims to describe how sharia contracts such as rahn and ijarah contracts are applied in pawnshops, while understanding the important role of sharia pawnshop institutions. Using a qualitative approach and literature review methods, this study explores the sharia principles applied in pawnshops. Data were obtained from various primary sources such as the Qur'an, Hadith, fatwas from scholars, and several articles in journals. The findings indicate that sharia pawnshops emphasize the principles of justice and mutual assistance, which is different from the conventional approach that uses interest as its basis. Sharia pawnshops offer an interest-free loan scheme that focuses on the maintenance costs of collateral. They reject the practices of usury, speculation, and uncertainty. This study suggests improving community welfare by optimizing the operations of sharia pawnshops through sharia-based financing services